WORKSHOP INTERNASIONAL STEM EDUCATION: INTEGRASI SCIENCE, TECHNOLOGY, SOCIETY, AND ENVIRONMENT UNTUK MENINGKATKAN TPACK GURU - Agus Suyatna; Abdurrahman Abdurrahman; I Wayan Distrik; Hervin Maulina; Novinta Nurulsari (Universitas Lampung, 2022)
Science, Technology, Engineering, and Mathematics (STEM) education has recently become the most trending issue in the world of education. STEM education is considered to be able to overcome real problems that occur in society. Integrating Science, Technology, Engineering, and Mathematics into the learning and teaching process is inevitable in this modern world, so all teachers need to master Technology Pedagogical Content Knowledge (TPACK) with confidence. Unfortunately, the approach to teacher education programs in many countries, particularly in Indonesia, has not yet integrated TPACK into the curriculum. To improve the quality of in-service teacher teaching competencies, the TPACK framework can be used as a reference and adoption in learning. Therefore, an international workshop on STEM education was held: integrating science, technology, society, and the environment for the development of TPACK activities for in-service teachers. The result of this workshop is an increase in inservice physics teacher TPACK (as a participant) in integrating science, technology, society, and the environment. STEM education can be done by conducting a kind of workshop that explains clearly and provides experience for all participants. In addition, it can be seen that the supporting and inhibiting factors for the implementation of the inservice physics teacher workshop in integrating science, technology, society, and the environment in STEM education with respect are knowledge and technology and the inhibiting factor is that in-service teachers do not have enough time to carry it out, especially during the pandemic covid-19.Keywords: inservice physics teacher; STEM; TPACK AbstrakPendidikan Science, Technology, Engineering, and Mathematics (STEM) akhir-akhir ini menjadi isu yang paling trending di dunia pendidikan. Pendidikan STEM dinilai mampu mengatasi permasalahan nyata yang terjadi di masyarakat. Mengintegrasikan Science, Technology, Engineering, and Mathematics ke dalam proses pembelajaran dan pengajaran tidak dapat dihindari di dunia modern ini, sehingga sangat penting bagi semua guru untuk menguasai Pengetahuan Konten Pedagogis Teknologi (TPACK) dengan percaya diri. Sayangnya, pendekatan terhadap program pendidikan guru di banyak negara, khususnya di Indonesia, belum mengintegrasikan TPACK ke dalam kurikulum. Untuk meningkatkan kualitas kompetensi mengajar inservice teacher, kerangka TPACK dapat menjadi acuan dan adopsi dalam pembelajaran. Oleh karena itu, diadakan lokakarya internasional pendidikan STEM: mengintegrasikan ilmu pengetahuan, teknologi, masyarakat, dan lingkungan untuk pembinaan kegiatan TPACK guru inservice. Hasil dari workshop ini adalah peningkatan inservice physics teacher TPACK (sebagai peserta) dalam mengintegrasikan ilmu pengetahuan, teknologi, masyarakat, dan lingkungan Pendidikan STEM dapat dilakukan dengan melakukan semacam workshop yang menjelaskan secara jelas dan memberikan pengalaman bagi semua peserta. Selain itu, dapat diketahui faktor pendukung dan penghambat pelaksanaan workshop inservice physics teacher dalam mengintegrasikan sains, teknologi, masyarakat, dan lingkungan dalam Pendidikan STEM dengan hormat adalah pengetahuan dan teknologi dan faktor penghambatnya adalah guru dalam jabatan tidak memiliki cukup waktu untuk melaksanakannya terutama di masa pandemi covid-19. DOI: https://doi.org/10.23960/rp/v2i1.hal.56-65